Metamaterial-Inspired Vacuum Electron Devices and Accelerators - Duan Z.; Shapiro M.A.; Schamiloglu E.; Behdad N.; Gong Y.; Booske J.H.; Basu B.N.; Temkin R.J. (My University, 2025)
Metamaterials (MTMs) are structured materials with subwavelength features that can be engineered to have some unique properties not found in nature, such as negative refractive index, reversed Doppler effect, and reversed Cherenkov radiation. Based on these novel MTMs, several important research groups have made great attempts to develop novel MTM-inspired vacuum electron devices (VEDs) and accelerators. Just as solid-state power devices are innovated by incessant emerging of new semiconductor materials, VEDs can also be inspired by MTMs to have very remarkable advantages, such as smaller size, higher power, higher efficiency, and/or larger gain relative to conventional VEDs, such as traveling-wave tubes, backward-wave oscillators, and klystrons. Similarly, relative to conventional accelerators, MTM-inspired accelerators have obvious advantages, such as smaller size and higher accelerating gradient. Furthermore, MTM-inspired devices have promising applications in areas such as radar, communication, electronic warfare, microwave heating, and imaging. © 1963-2012 IEEE.